2021
DOI: 10.1186/s12905-021-01529-5
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to seeking post-abortion care in Paktika Province, Afghanistan: a qualitative study of clients and community members

Abstract: Background Unsafe abortion is a leading cause of maternal mortality. In Afghanistan, which has experienced decades of armed conflict and where abortion is highly restricted, maternal mortality is high at 638 maternal deaths per 100,000 live births. Post-abortion care (PAC) is a lifesaving package of interventions to reduce morbidity and mortality related to induced or spontaneous abortion, but is rarely provided and often of poor quality, particularly in humanitarian settings. In July 2018, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 48 publications
0
7
0
Order By: Relevance
“…Quinn and Chaudior found that women delay seeking postabortion care if stigmatized because they were protecting themselves from being the victims of discrimination [40]. This was confirmed by Perera et al and Yegon et al that stigma and poverty, nonetheless, also played a vital role in influencing the decision-making process [6,41]. Demtsu et al reported an association between the provision of PAC services, religious, cultural beliefs, morals, and values in terms of care of women seeking PAC services [42].…”
Section: Discussion Of Findingsmentioning
confidence: 87%
See 2 more Smart Citations
“…Quinn and Chaudior found that women delay seeking postabortion care if stigmatized because they were protecting themselves from being the victims of discrimination [40]. This was confirmed by Perera et al and Yegon et al that stigma and poverty, nonetheless, also played a vital role in influencing the decision-making process [6,41]. Demtsu et al reported an association between the provision of PAC services, religious, cultural beliefs, morals, and values in terms of care of women seeking PAC services [42].…”
Section: Discussion Of Findingsmentioning
confidence: 87%
“…One of the main challenges for women who access PAC services in KZN is the long distances they have to travel to access proper care in the hospital; poor roads and transportation further complicate this in their areas. This was corroborated by Perera et al that delays in care-seeking due to various reasons, including lack of transport and concerns about costs [6]. Literature shows that increased distance to health facilities and poor local transportation impedes accessibility to the primary and secondary health care services as well as that the delayed health care provision can worsen people's health [11,12].…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…Others highlighted a lack of health providers knowledge regarding manual vacuum aspiration (MVA) which is a recommended instrumental technology to evacuate the uterus (instead of the dilatation and sharp curettage (D&C)) [16]. Health providers' negative attitudes were also found to limit women's autonomy regarding their sexual and reproductive health needs [15,17]. Studies assessing interventions showed that the support of PAC services by non-governmental organizations (NGO) increased post-abortion contraception counselling and uptake [19,20], enhanced providers' use of appropriate technologies (MVA) [18][19][20] and changed their attitude towards a right-based, non-judgmental approach to women [18] leading to an overall positive experience of care for patients [21].…”
mentioning
confidence: 99%
“…Studies assessing interventions showed that the support of PAC services by non-governmental organizations (NGO) increased post-abortion contraception counselling and uptake [19,20], enhanced providers' use of appropriate technologies (MVA) [18][19][20] and changed their attitude towards a right-based, non-judgmental approach to women [18] leading to an overall positive experience of care for patients [21]. All but one [14] of these studies assessed only some of Donabedian's three conceptual domains: either inputs of care (facility equipment, supplies and human resources capacity to provide PAC) [13,15,18], indicators of provision of care (number of PAC, MVA use and contraception uptake) [20], patients' experience of care [17] or a combination of the latter two components of the process of care [19,21].…”
mentioning
confidence: 99%